Penciptaan Gambar Ilustrasi Untuk Meningkatkan Personal Branding CV Pustaka Cemerlang (International Forum of Researchers and Lecturers, 2024)
Humans as a visual creature has the ability to process visual data better than other kinds of data. Therefore in this on going developing digital era the use of digital illustration is considered more beneficial and effective as promoting media. This journal will discuss the connection between illustration and the company's personal branding especially illustration as its visual, concept, theme, idea, story or text presentation media. Illustration is considered as an effective way in deliberating a complex concept to readers or consumers. That is why illustration can be a one of the effective design elements to expose and explain company's values and characters. By using illustration pictures, companies can drag more the audience's attention.